Phrygian Glosses in Pseudo-Plutarch’s Work De Fluviis - Kaczyńska, Elwira (Lingua Posnaniensis, 2011)
The aim of my study is to discuss three Phrygian glosses attested in Pseudo-Plutarch's work Περιπoταμων and explain them from the etymological and historical-comparative point of view. It is concluded finally that all the glosses should be regarded as a real and valuable part of the Phrygian language.